DETERMINAN TENAGA KERJA TERDIDIK BEKERJA SEBAGAI KARYAWAN (Studi Kasus Lulusan S1 Fakultas Ekonomi Universitas Riau Tahun 2010) - Hubert Marpaung; Rahmita budiartiningsih; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is conducted to educated labour of graduated from the Faculty of Economics, University of Riau 2010, as a mean to know the educated labour determinant work as employees. The number of respondents who specified as many as 85 respondents. Determination the number samples done by using the formula Slovin from 545 population representing grand total of graduates of the Faculty of Economics, University of Riau 2010. Data analysis method used in this research is descriptive method that is study the problems by describing and explaining the basis of data obtained so that can an idea of the problems which in fact.The results of rescarch indicate that, the educated labour determinant work as an employees, to fulfill the it’s life requirement or to earn life sclected by 52.94% of respondents, that is through nominal of obtained wage, which is also related to the position on a job as an employee, to get job security, as many as 77.65% of respondents opinion worked as an employee has a good position in society, and 75.29% of respondents worked as an employee caused by hereditary factors.Keywords: Educated Labour, Employment, Employee.